2011
DOI: 10.1074/jbc.m110.184374
|View full text |Cite
|
Sign up to set email alerts
|

G-actin Participates in RNA Polymerase II-dependent Transcription Elongation by Recruiting Positive Transcription Elongation Factor b (P-TEFb)

Abstract: Actin is a key regulator of RNA polymerase (Pol) II-dependent transcription. Positive transcription elongation factor b (P-TEFb), a Cdk9/cyclin T1 heterodimer, has been reported to play a critical role in transcription elongation. However, the relationship between actin and P-TEFb is still not clear. In this study, actin was found to interact with Cdk9, a catalytic subunit of P-TEFb, in elongation complexes. Using immunofluorescence and immunoprecipitation assays, Cdk9 was found to bind to G-actin through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 54 publications
(60 reference statements)
1
57
0
1
Order By: Relevance
“…Nuclear actin is a key regulator of polymerase II-dependent transcription and is required for RNA polymerase I transcription [43][44]. Zhang et al showed the localization of FUrd in the nucleoli and connected this with active RNA polymerase I transcription [45].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear actin is a key regulator of polymerase II-dependent transcription and is required for RNA polymerase I transcription [43][44]. Zhang et al showed the localization of FUrd in the nucleoli and connected this with active RNA polymerase I transcription [45].…”
Section: Discussionmentioning
confidence: 99%
“…regulates the recruitment of Pol II (Tang et al 2009). Moreover, β-actin is also involved in transcription elongation by interacting with Cdk9 (Qi et al 2011). In this study, we treated HepG2 cells with IL-6 to induce gene expression and measured the expression of the targeting gene p21.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that actin is a component of the chromatin remodeling complex, associates with hnRNP and acts as a platform for the recruitment of HAT or HDAC complexes to the active transcription unit (Dingova et al 2009). Previous studies in our lab have demonstrated that β-actin is required for the initiation and elongation steps of transcription (Tang et al 2009;Qi et al 2011). To evaluate whether β-actin regulates gene transcription directly, we built an IL-6-induced gene expression model in HepG2 cells and targeted p21 as an endogenous gene.…”
Section: β-Actin Regulates the P21 Expression Induced By Il-6mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous Arps have been described in the nucleus (reviewed by Oma and Harata, 2011). Actin and Arps recruit chromatin remodeling complexes (Kukalev et al, 2005;Obrdlik et al, 2008;Qi et al, 2011;Blessing et al, 2004), and chromatin remodeling complexes associate with Arp4 and actin (Blessing et al, 2004). The nucleating activity of Arp2/3 is stimulated by Wiskott-Aldrich syndrome family proteins (WASPs), and both Arp2/3 and neural WASP (N-WASP) are found in the nucleus.…”
Section: Nuclear Actin and Transcriptionmentioning
confidence: 99%